Communication Strategy of the Ministry of Communication and Information Technology in Preventing the Spread of Hoax on Social Media - Andre Ikhsano; Denise Ferinda Sutanto; Yolanda Stellarosa (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Social media offers various interesting features with their respective advantages, such as a medium for communicating, making transactions, building communities, learning, and running a business. These features can be accessed anywhere and anytime, with only an electronic device and an internet connection. However, with these various advantages and conveniences, not a few people abuse social media by spreading fake news or hoaxes. One of the government institutions in Indonesia that has duties and functions in stopping, monitoring, and preventing the spread of hoaxes is the Ministry of Communication and Informatics (Kemkominfo). This study aims to analyze the communication strategy of the Ministry of Communication and Informatics  to prevent the spread of hoaxes on social media. This research uses a qualitative descriptive method and data is collected through interviews with two internal parties of the Directorate General of Information and Public Communication at  the Ministry of Communication and Informatics; and communication specialists. The results showed that the communication strategy implemented by the Ministry of Communication and Informatics to prevent the spread of hoaxes on social media was to use digital literacy.There are four (4) pillars that are the main points in the digital literacy program, namely digital security, digital ethics, digital culture, and digital skills.